2008
DOI: 10.1039/b712837a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fluorination on the luminescent behaviour of 8-hydroxyquinoline boron compounds

Abstract: A series of boron quinolinate compounds with different degrees of fluorination {Ph 2 BQ 1, (4-F-C 6 H 4 ) 2 BQ 2 and (C 6 F 5 ) 2 BQ 3 (where Q is 8-quinolinoate)} have been However, when the boron compounds 1, 2 or 3 are doped into a (4,4'-bis(carbazol-9-yl)diphenyl (CBP) host, emission solely attributable to 1-3 is observed. In such devices, the boron compounds 1 and 2 outperform AlQ 3 as an emitter at low to moderate current densities.2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 43 publications
1
25
0
1
Order By: Relevance
“…These values are lower than those reported for related diarylborinic 8-oxyquinolinates (ca. 37,38 In contrast to the case of 1 and 10, it was recently reported that the replacement of Ph 2 B with a (C 6 F 5 ) 2 B moiety in diarylboron diketonates resulted in the increase of λ em by ca. 2, 26 We have observed that the 1 H NMR chemical shifts of aldimine protons (CHvN) in 1-7 (solvent: acetone-d 6 ) correlate strongly (R 2 = 0.95) with Hammett σ p − constants of R′ substituents 34,35 attached to the salicydene fragment at the 6-position (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 93%
“…These values are lower than those reported for related diarylborinic 8-oxyquinolinates (ca. 37,38 In contrast to the case of 1 and 10, it was recently reported that the replacement of Ph 2 B with a (C 6 F 5 ) 2 B moiety in diarylboron diketonates resulted in the increase of λ em by ca. 2, 26 We have observed that the 1 H NMR chemical shifts of aldimine protons (CHvN) in 1-7 (solvent: acetone-d 6 ) correlate strongly (R 2 = 0.95) with Hammett σ p − constants of R′ substituents 34,35 attached to the salicydene fragment at the 6-position (Fig.…”
Section: Synthesis and Characterizationmentioning
confidence: 93%
“…2000 cd·m −2 and current efficiencies above 1 cd·A −1 . It should be stressed that such good parameters were achieved with diodes containing only 2 wt% of emitter in the matrix whereas in previous reports much higher emitter contents (above 10 wt%) were used 72. It may be the case that the promising optical properties of 1-5 are a consequence of a cooperation of two Q chromophores present in the molecular structure.…”
mentioning
confidence: 94%
“…[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Among the tetracoordinate boron compounds, boron dipyrromethene dyes ( Figure 1, A) [32][33][34][35] have been studied to a greater extent owing to their potential application in artificial light harvesters, fluorescent sensors, laser dyes, sensitizers for solar cells, and molecular photonic wires. Boron quinolate compounds are analogous to aluminum quinolato compounds ( Figure 1, B); [26,[36][37][38][39][40][41][42] the photophysical tuning of R 2 BQ compounds (Q = substituted quinolate) was recently studied by Wang and co-workers [40,41] and Jaekle and coworkers. [43][44][45][46] Schiff base boron compounds ( Figure 1, C) are yet another type of four-coordinate boron complex that has gained interest owing to their greater stability than tricoordinate boron compounds.…”
Section: Introductionmentioning
confidence: 99%